WebQual 4.0 dan Importance-Performance Analysis (IPA) : Eksplorasi Kualitas Situs Web e-Kuisioner - Ismail Ismail; Fauzan Putraga Al-Bahri (KITA Institute, 2019)
The e-questionnaire application that researchers built using CodeIgniter and React-Js which serves to support researchers' activities to survey respondents online and various evaluations of the quality of the application need to be carried out in accordance with the expectations of users, one of which is to analyze the quality of the website using the method WebQual 4.0 with the Importance-Performance Analysis (IPA) approach. The research method used by researchers is a survey method using the WebQual 4.0 method and Importance-Performance Analysis (IPA) to measure the level of performance and importance on the e-Karis website. The results of this study found that the level of importance and level of performance on the e-Questionnaire website that needs to be maximized in ease of use, appearance, and improvement on the information and communication pages that must be considered by the manager of the E-Questionnaire website.